Identification of polyphenol from Ziziphi spinosae semen against human colon cancer cells and colitis-associated colorectal cancer in mice. Issue 9 (7th September 2020) - Shan, Shuhua; Xie, Yue; Zhang, Chengying; Jia, Bin; Li, Hanqing; Li, Zhuoyu
Abstract : Spinosin derived from homology of medicine and food-zizyphi spinosi semen (ZSS) exhibits a new pharmacological property against colon cancer. Abstract : Homology of medicine and food-zizyphi spinosi semen (ZSS) exhibits abundant pharmacological activities, such as sedation, hypnosis and anti-depression. In the present study, the water soluble polyphenols extracted from ZSS via the acid digestion method were named ZSSP, and exhibited significant anti-colorectal cancer (CRC) activity, characterized by restraining cell proliferation, promoting cell apoptosis and increasing chemo-sensitivity of CRC cells. The potential of ZSSP in vivo was further evaluated in an AOM/DSS-induced colitis-associated carcinogenesis (CAC) mouse model. Intriguingly, ZSSP diminished the number and volume of CAC polyps in mice in a dose-dependent manner, and effectively limited the damage of mice organs induced by AOM/DSS. The immunohistochemistry result showed that the elevated CRC early markers in CAC mice, such as COX-II, EMR1, and Ki67, were potently prevented by the ZSSP treatment. Further, the component in ZSSP with the anti-CRC activity was identified as spinosin by the macroporous resin of SP207 and RP-HPLC-MS/MS. Interestingly, during the extraction process, sodium ions were introduced forming spinosin·Na +, which had better water solubility and more remarkable anti-CRC activity than the spinosin. This study provides a new pharmacological property of spinosin derived from ZSS, inhibiting the growth of human CRC cells and colitis-associated CRC in mice, which indicates its potential use as a natural agent against CRC.